Age-Friendly Cities - Hamdüsena Eşrefoğlu (Senectus)
This paper discusses the need to adapt urban environments to the growing needs of an aging population through the development of age-friendly cities. The article highlights the need for initiatives that are inclusive of older people, recognizing that the demographic shift is towards an older global population and that older adults can contribute better to society when supported by appropriate urban designs and policies. Those studies have revealed both the successes and challenges that have occurred when creating environments where older adults can thrive, as well as how collaboration between local governments and a range of stakeholders have focused on building the capacity of local government officials and sharing knowledge about building effective age-related services and community infrastructure. The study has revealed a marked difference between the well-established planning processes for young people and families and those for the aging population, highlighting the need for more comprehensive and measurable age-friendly policies and infrastructure. The paper also highlights that current economic constraints on government budgets require innovative approaches to designing policies that can promote aging in place and suggests that lifelong neighborhoods and age-friendly communities can serve as models for such policies.